Determining the nature and spatial-temporal changes of the livelihood asset pentagon and its relationship with livelihood opportunities in Ghana. Issue 4 (8th August 2019) - Mahama, Tiah A-K; Maharjan, Keshav L.
ABSTRACT: The Sustainable Livelihood Framework (SLF) operationalizes the concept of sustainable livelihood as introduced by Chambers and Conway. The framework's centerpiece is the asset pentagon. Whereas there is a plethora of studies that are based on the framework, a limited number of them focus on determining the nature of the asset pentagon. This is on the back of the fact that different shapes of the pentagon abound for different contexts. We constructed an asset pentagon for Ghana with the aid of the principal component analysis, using secondary data and consequently, modified the SLF for the Ghanaian context. We also examined how assets determine livelihood opportunities. The results show that Ghana has an irregular asset pentagon characterized by spatial-temporal changes. Spatially, differences exist in asset possession and that explains differential livelihood opportunities. The study contributes to understanding the nature of the asset pentagon in Ghana as well as elaborates extant literature.